Germination and plantlet regeneration of encapsulated microshoots of aromatic rice (Oryza sativa L. Cv. MRQ 74) - Taha, R.M.; Saleh, A.; Mahmad, N.; Hasbullah, N.A.; Mohajer, S. (2012)
Plant tissues such as somatic embryos, apical shoot tips, axillary shoot buds, embryogenic calli, and protocom-like bodies are potential micropropagules that have been considered for creating synthetic seeds. In the present study, 3-5 mm microshoots of Oryza sativa L. Cv. MRQ 74 were used as explant sources for obtaining synthetic seeds. Microshoots were induced from stem explants on Murashige and Skoog (MS) medium supplemented with 1.5 mg/L benzylaminopurine (BAP). They were encapsulated in 3% (w/v) sodium alginate, 3% sucrose, 0.1 mg/L BAP, and 0.1 mg/L α-Naphthalene acetic acid (NAA). Germination and plantlet regeneration of the encapsulated seeds were tested by culturing them on various germination media. The effect of storage period (15-30 days) was also investigated. The maximum germination and plantlet regeneration (100.0%) were recorded on MS media containing 3% sucrose and 0.8% agar with and without 0.1 mg/L BAP. However, a low germination rate (6.67%) was obtained using top soil as a sowing substrate. The germination rate of the encapsulated microshoots decreased from 93.33% to 3.33% after 30 days of storage at 4°C in the dark. Therefore, further research is being done to improve the germination rate of the synthetic seeds.